2022
DOI: 10.1186/s12913-022-08348-w
|View full text |Cite
|
Sign up to set email alerts
|

Combined impact of Medicare’s hospital pay for performance programs on quality and safety outcomes is mixed

Abstract: Background Three major hospital pay for performance (P4P) programs were introduced by the Affordable Care Act and intended to improve the quality, safety and efficiency of care provided to Medicare beneficiaries. The financial risk to hospitals associated with Medicare’s P4P programs is substantial. Evidence on the positive impact of these programs, however, has been mixed, and no study has assessed their combined impact. In this study, we examined the combined impact of Medicare’s P4P programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…More positive, although less comparable findings were reported in studies evaluating the impact of the quality assessment systems in Taiwan [28] and Iran [29], while no improvements, or very mixed results were reported in the USA by the Centers for Medicare and Medicaid Services (CMS) [30]. Between 2012 and 2014, the CMS started three programs that adjusted Medicare hospital payments through rewards and penalties, aiming to reduce readmissions and hospital-acquired conditions, and to promote valuebased purchasing [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More positive, although less comparable findings were reported in studies evaluating the impact of the quality assessment systems in Taiwan [28] and Iran [29], while no improvements, or very mixed results were reported in the USA by the Centers for Medicare and Medicaid Services (CMS) [30]. Between 2012 and 2014, the CMS started three programs that adjusted Medicare hospital payments through rewards and penalties, aiming to reduce readmissions and hospital-acquired conditions, and to promote valuebased purchasing [31].…”
Section: Discussionmentioning
confidence: 99%
“…Between 2012 and 2014, the CMS started three programs that adjusted Medicare hospital payments through rewards and penalties, aiming to reduce readmissions and hospital-acquired conditions, and to promote valuebased purchasing [31]. A pre-post evaluation (2007-2016) of administrative datasets from 14 States found extremely mixed results in the hospital quality and safety indicators that were targeted by the three programs [30]. Interestingly, another assessment found penalties to be associated with environmental and social characteristics that hospitals cannot control-i.e., medical complexity, uncompensated care and the portion of population who live alone [31].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Medicare assessed $949 million in penalties under the 3 programs-HRRP, HACRP, and HVBP. 8 The CNS influences the quality of care at the bedside and can impact the perception of care from the patient perspective. Through a quality and safety lens, the CNS is at the forefront to increase the return on investment for hospitals as they work closely with the clinical staff and the management.…”
Section: Discussionmentioning
confidence: 99%
“…The financial risk to hospitals is significant. In 2019, Medicare assessed $949 million in penalties under the 3 programs—HRRP, HACRP, and HVBP 8 . The CNS influences the quality of care at the bedside and can impact the perception of care from the patient perspective.…”
Section: Discussionmentioning
confidence: 99%
“…To date, available evidence on whether hospital-based VBP programs achieved their primary quality and cost reduction goals is mixed ( 12 , 23 ). Many studies have found improvements in health care quality in certain cases even though the effects on cost containment appear to have been modest ( 4 , 24 26 ).…”
Section: Background and Introductionmentioning
confidence: 99%